1999
DOI: 10.1038/sj.onc.1202781
|View full text |Cite
|
Sign up to set email alerts
|

Mdm2 binds p73α without targeting degradation

Abstract: The function of the p53 tumor suppressor protein is regulated by interaction with Mdm2, which targets p53 for ubiquitin dependent degradation. We show here that like p53, p73a forms an interaction with Mdm2, both in vitro and in cells, but this does not result in the degradation of the p73a protein. The human papillomavirus E6 protein also fails to degrade p73a, suggesting that the mechanisms governing p73a stability are distinct from those known to regulate p53 stability. However, the interaction of Mdm2 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
161
1
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(174 citation statements)
references
References 25 publications
11
161
1
1
Order By: Relevance
“…55 p73 is also able to bind to MDM-2, but is not degraded and so cannot be stabilised by ARF expression. 56 This provides a direct mechanism for E2F-1-induced cell death, and although p73 is not frequently mutated in human tumours, methylation-dependent silencing has been reported in haematological malignancies. 57 Moreover, it has recently been shown that several tumour-derived mutants of p53 that are often retained in cancer are able to bind and inactivate p73, thereby circumventing the necessity to mutate p73 per se.…”
Section: A Role In Cancermentioning
confidence: 99%
“…55 p73 is also able to bind to MDM-2, but is not degraded and so cannot be stabilised by ARF expression. 56 This provides a direct mechanism for E2F-1-induced cell death, and although p73 is not frequently mutated in human tumours, methylation-dependent silencing has been reported in haematological malignancies. 57 Moreover, it has recently been shown that several tumour-derived mutants of p53 that are often retained in cancer are able to bind and inactivate p73, thereby circumventing the necessity to mutate p73 per se.…”
Section: A Role In Cancermentioning
confidence: 99%
“…HDM2 has also been shown to functionally interact with other proteins including p14ARF, Rb, E2F-1 (Iwakuma and Lozano, 2003) and p21 (Zhang et al, 2004). Furthermore, when overexpressed, HDM2 also binds to other p53 family members p73 (Balint et al, 1999) and p63 (Kadakia et al, 2001). Like p53, p73 binds to the N-terminal TA domain of HDM2 resulting in suppression of p73 transcriptional activity (Balint et al, 1999;Zeng et al, 1999).…”
mentioning
confidence: 99%
“…Furthermore, when overexpressed, HDM2 also binds to other p53 family members p73 (Balint et al, 1999) and p63 (Kadakia et al, 2001). Like p53, p73 binds to the N-terminal TA domain of HDM2 resulting in suppression of p73 transcriptional activity (Balint et al, 1999;Zeng et al, 1999). HDM2 mutants lacking amino acid residues 58-89 do not interact with either p53 or p73, suggesting that both p53 and p73 bind to a similar region at the N-terminus of HDM2 (Balint et al, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While p53 is degradated by binding to its E3 ligase MDM2, MDM2 binding to p73 disrupts its interaction with p300/CBP, but does not mediate p73 degradation. [20][21][22] Instead, p73 degradation is linked to SUMO-1 modification which renders it proteasomedegradable. 23 It is possible that hetero-oligmerization prevents sumoylation of p73, thereby stabilizing it.…”
mentioning
confidence: 99%